GLASS FIBRE REINFORCED PRECAST CONCRETE CONTAINING HIGH CONTENT POZZOLANIC MATERIALS - Amed, Bahadur; Kabay, Nihat (YILDIZ TECHNICAL UNIV, 2019)
Glass fiber reinforced concrete (GFRC) is a composite construction material widely used as a precast exterior element in the construction industry. GFRC is generally composed of mixture of cement, sand, water and glass fiber. Cement production causes high energy consumption and CO2 emissions, which has negative impacts on the environment. Therefore, in this study, the effect of using high amount of fly ash and blast furnace slag from industrial waste materials instead of cement is investigated. The cement was replaced by fly ash and blast furnace slag in different ratios and the fresh, physical and mechanical properties of 6 different GFRC mixes were investigated. In addition, SEM micrographs were taken after the bending test to analyze the microstructure of GFRC. Test results showed that the workability of mixtures was modified by pozzolan addition. Fly ash improved the workability of GFRC matrix, however synergistic effect of fly ash and slag tend to insignificantly affect the workability. The water absorption of mixtures was found as 11 +/- 3% and the densities varied between 1910 and 2000 kg/m(3). Substitution of cement with fly and slag reduced the early age flexural strength of the mixtures, the increase in fiber content resulted in improved flexural strength and the highest strength was observed in C100F0S0G4 mix as 12.2 MPa.
Keywords: Glass fiber reinforced concrete; fly ash; slag; sustainability; microstructure; FLY-ASH; CEMENT; GRC; Engineering